Bregmosina, a new Neotropical genus of Limosininae (Diptera: Sphaeroceridae) - Marshall, Stephen A. (Zootaxa, 2013)
Bregmosina, a new genus of Limosininae (Diptera, Sphaeroceridae), is described on the basis of five new species from Central and South America. The genus is characterized by a broad head, swollen face, large oral cavity, a single pair of very large cruciate interfrontal bristles, short, broad fore tarsomeres and swollen hind tarsomeres one and two. The unusual male genitalia, including a longitudinally split sternite 5, strongly indicate that the genus is monophyletic. All species are probably associated with treefalls.